Pergeseran Nilai Sosial pada Hak Waris Perempuan Karo Muslim di Desa Budaya Lingga Kabupaten Karo - Lediyana Br Kaban; Suheri Harahap; Ahmed Fernanda Desky (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the shift in social values in the inheritance rights of Karo Muslim women in Lingga Culture Village, Karo Regency. This research uses qualitative research and descriptive method. Information was collected through observation, in-depth interviews with traditional leaders, religious leaders, and Karo Muslim family members and documentation. The findings of the study reveal that there is a significant change in the distribution of inheritance rights of Karo Muslim women, from previously not getting their share to now being more fair and equal. The patriarchal culture in Karo society places men at a higher level than women. The Lingga Cultural Village community initially applied customary law, namely